Clinical and audiological evaluation of post traumatic hearing loss - Shankar, Abhijit; George, Shibu; Somaraj, Satheesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Post traumatic hearing loss is one of the most common problems encountered among trauma victims. It can manifest as conductive, sensorineural or mixed hearing loss. It is against this background that the study evaluated the clinical and audiological outcome of 47 patients of trauma. Methods: A descriptive longitudinal study was conducted over a period January 2017 to March 2018. Follow up was done after 3 months of discharge. Study consisted of 47 patients presenting with features of trauma related injuries. After carrying out systematic clinical, audiometric and radiological evaluation, patients were managed conservatively. Results: Of the 47 patients studied, 89.98% were related to road traffic accidents (RTAs); and 76.60% were under the influence of alcohol at the time of trauma. Among the 32 cases of the RTAs involving two wheelers, 29 patients (90.62%) were not using protective devices like helmet. Nearly 90% of patients had temporal bone fracture. Audiological evaluation confirmed hearing loss in 77% of patients at presentation. There was significant improvement of hearing thresholds with 51% attaining normal hearing at follow up with conservative management. Conclusions: Post traumatic hearing loss was very common, conductive hearing loss being the most common type. It resolved over a few days to few weeks post injury. Timely diagnosis and management with early steroid therapy showed encouraging results for patients with traumatic sensorineural hearing loss or mixed hearing loss.